(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
Cognitive Behavioral Therapy (CBT) has been considered the gold-standard treatment to Acute Stress Disorder (ASD), with its use in ASD course mainly focusing the prevention of the development of Post Trauma-tic Stress Disorder (PTSD). However, there is no consensus about effective strategies into CBT approaches for ASD treatment. Thus, this article aims to identify the most efficient strategies in the CBT approach. In order to attend this purpose, a systematic review was conducted, looking for randomized clinical trials ad-dressing ASD treatment, on the following databases: Scielo, LILACS, MedLine / PubMed, Web of Science and PsychInfo in June 2012. Initially, 1103 studies were identified. After the adoption of the exclusion criteria, five studies were included in the review process. The results of the review point that exposure therapy have the most promising outcomes in ASD treatment. Furthermore, the review also indicates the need for studies with better methodological quality, as well as the use of broader samples.